The Use of Google Translate in EFL Essay Writing: Is It a Cheating? - Adelia Puspa; Dwi Bayu Saputra; Lia Haryana (English Franca: Academic Journal of English Language and Education, 2023)
During the process of writing an essay, many students are utilizing online translation tools like Google Translate due to the widespread availability of computing technology and the internet. Online translation programming is strong, yet it is inclined to over-exacting interpretation, and cannot represent the setting similar to a human interpreter. As a result, students are left to rely on a tool that promises to "do the hard work" for them by allowing them to only think and write in their native language. This study is aimed to determine the extent to which students at the University of Bengkulu, Indonesia, rely on technology in writing essays and whether they consider its use to be cheating or not. The data was obtained by conducting mixed-method research through survey with a closed-ended questionnaire and interview to the English Department students of Universitas Bengkulu who are currently taking a Critical Writing course. The results discovered that all of the participants have utilized GT as a translation tool for writing essays particularly to translate word from their first language into English. Moreover, they considered using GT for essay writing as cheating depending on how it is used; for graded assignments or writing test.